Unit Production of Apple Processing at State Vocational School 2, Batu - Endah Rahayu Lestari; Nur Hidayat; Wike Agustin Prima Dania (Journal of Innovation and Applied Technology, 2015)
Currently, unit productions of apple processing that have been developed by State Vocational School 2 Batu majoring in Agricultural Product Technology are apple chips, apple juice, and apple sweet with brand “ESEMKA”. The purpose of this activity is to expedite learning process, especially in agricultural processing practice by introducing me-chanical dryer in unit productions of apple processing at this school and mechanical mixer multi function in apple porridge production at SME “Bagus Agriseta Mandiri” that become practical place for the students. From the result of perfor-mance test of mechanical dryer to produce apple sweets with the water content of 12% is 15 hours therefore processing is more efficient and hygiene, which was previously done with the sun drying process which takes up to 3 days. However the application of mechanical mixer multi function at SME apple porridge stirring time of 3.5 hours/pro-cess, where pre-viously manual methods takes 6 hours/ process, so the efficiency of the mixing process increased up to 90% and less fuel. The application processing machines increase performan-ce of production also has implications that the teaching and learning process at this vocational school over a smooth and increase students' knowledge and skills.Keywords: apple, mechanical mixer, mechanical dryer